Review Artikel: Aktivitas Antibakteri Senyawa Metabolit Sekunder pada Beberapa Ekstrak Tanaman Terhadap Bakteri Gram Positif - Jofri, Dirga Hosea Seventeen; Kartika, Rudi; Aswat, Muhammad Raihan; Rizkirullah, Muhammad Adhitya; Kurniawan, Andi; Azka, Andi Aulia Urrahman (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Antibacterials are compounds used to eradicate microbes, especially microbes that harm humans. These antibacterial compounds can be extracted directly from plants, where these extracts contain secondary metabolite compounds that have antibacterial activity. Antibacterial testing is carried out on gram-positive bacteria such as Staphylococcus, Streptococcus and others. The method used in this research was a literature study of 10 national and international articles published in the last 10 years. The articles cited focus on research articles on plants that have the potential as antibacterials of several gram-positive bacteria which include extract solvents, metabolite compound content in extracts and their activity capabilities based on the diameter value of the inhibition zone and/or minimum inhibitory concentration using the disc diffusion method. Keywords : Antibacterial, Diffusion Discs, Gram Positive, Secondary Metabolites